Collective action on an individual and local scale: sociological profiles and portraits - Nunes, N.; Cachado, R.; Raposo, Otávio; Ferreira, D.; Carmo, R. M. (Sociologia, Problemas e Práticas, 2016)
This article analyzes the dispositions towards collective action, especially in regards to the local and individual scales. We focus mainly on the plurality of the individual situations, paying attention to the role of the local contexts to the greater or lesser incorporation of a radical habitus. In depth interviews were done to 15 individuals belonging to nine households living in three municipalities of the Lisbon Metropolitan Area, from which were built profiles and sociological portraits which salient the relevance of socializations, sociability and the involvement in collective actors in the dispositions for the collective action.